Leprosy: prevalence and factors associated with seropositivity for anti-NDO-LID antibodies in children under 15 years of age - Luciane Cardoso Gomes; Denise da Costa Boamorte Cortela; Eliane Aparecida Silva; Ageo Mário Cândido da Silva; Silvana Margarida Benevides Ferreira (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: A high prevalence of leprosy among children under 15 years of age indicates the need to implement actions to prevent new cases of the disease. Serological tests have been developed with the aim of helping to control the disease by indicating, through seropositivity, the presence of infection. Objective: To analyze the prevalence and factors associated with seropositivity rate for anti-NDO-LID antibodies in children under 15 years of age, contacts of leprosy patients. Method: We performed a cross-sectional study with 210 children under 15 years old of age. Of them, 50 were household contacts and 160 were neighborhood contacts living in the municipality of Cuiabá, state of Mato Grosso, in 2016. The data were obtained from interviews and the NDO-LID rapid test during home visits from February to July 2016. For the analysis, we used Poisson regression and prevalence ratio. Results: Seropositivity in contacts was 6.2%. Variables associated with seropositive tests included sex (PR = 1.05; 95% CI: 1.01 - 1.08), race/skin color (PR = 0.95; 95% CI: 0.90 - 0.99), residence area (PR = 1.05; 95% CI: 1.01 - 1.09), and number of people per household (PR = 1.06; 95% CI: 1.02 - 1.08). Study Limitations: The small sample size, besides leading to wide confidence intervals, may have been a limitation for the identification of associated factors. Conclusions: The prevalence of seropositivity was high. Variables associated with NDO-LID seropositivity included female sex, not to be brown skinned, live in urban areas, and live with five or more people.